First publication of the diary of Yu.A. Smirnov-Nesvitsky - D. D. Kumukova (Шаги)
The following publication is a collection of excerpts from a diary kept between 1961 and 2005 by Yu.A. Smirnov-Nesvitsky — Dr. Sci. (Art History), theatre historian, stage director, playwright, founder of the “Subbota” (“Saturday”) authors’ theatre, Honoured Artist of the Russian Federation. Across the pages of the diary are scattered the names of various theater personalities — N.P. Akimov, V.N. Pluchek, G.A. Tovstonogov, O.N. Efremov, A.M. Volodin, O.P. Tabakov, A.A. Mironov; theatre historians and theorists S.L. Tsimbal, R.M. Beniash, V.M. Krasovskaya, D.I. Zolotnitsky, G.A. Lapkina, S.V. Vladimirov, V.A. Sakhnovsky-Pankeev, and many others, whom fate brought together with Smirnov-Nesvitsky. He keeps records of discussions of Moscow and St. Petersburg premieres, put on by the professional community of the time; recounts “Subbota’s” many-year struggle to stand up for its own voice, and tells many creative, scientific and human stories of his own life, and of the times in general.